Analisis Kritik Sosial dalam Kumpulan Cerita Pendek Dijamin Bukan Sihir Karya Musmarwan Abdullah (Tinjauan Sosiologi Sastra) - Ilman Tawabi; Suntoko Suntoko; Wienike Dinar Pratiwi (Peneliti.net, 2021)
The choice of literature as a solution to people's dependence on gadgets and to overcome the level of politeness, because audio-visual literacy offered on electronic devices or social media is deemed unable to produce the expected results as a substitute for text (literary) literacy. This study uses a sociology of literature approach, and uses qualitative research methods. In this study, 10 stories containing social criticism were selected from the collection of stories Dijamin Bukan Sihir by Musmarwan Abdullah. Data collection techniques in this study used document content analysis techniques by reading, recording, and analyzing data. While the data analysis technique in this study uses the Miles and Huberman model, so that the activities in data analysis in this study are data reduction, data display, and conclusion drawing/verification. Based on the results of the analysis conducted by the researchers, there are six aspects of social criticism contained in the collection of short stories Dijamin Bukan Sihir by Musmarwan Abdullah, including social criticism of political problems, social criticism of cultural problems, social criticism of economic problems, social criticism of technology problems, social criticism family problems, social criticism of religious issues.